2015
DOI: 10.5539/jedp.v5n2p119
|View full text |Cite
|
Sign up to set email alerts
|

Trait Emotion, Emotional Regulation, and Parenting Styles

Abstract: The present study investigated relations among parenting styles and emotion regulation, trait emotion, and general well-being among 153 emerging adults. Two path models were tested, finding that parenting styles contributed to multiple pathways to emotional regulation. As expected, not only did participants who reported high levels of authoritative parenting endorse high levels of positive emotion, they also reported lower levels of emotional control and emotional self-awareness. These low levels were, in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Research conducted in Australia-Indonesia showed that children with authoritarian parenting style have low emotion regulation and higher behavioral problems [20]. Children with authoritarian parenting are predicted to be poor at regulating emotions which leads to less positive emotions, higher negative emotions, and behavioral problems [21]. However, another study conducted in Pakistan stated that authoritarian parenting is not significantly correlated with emotion regulation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Australia-Indonesia showed that children with authoritarian parenting style have low emotion regulation and higher behavioral problems [20]. Children with authoritarian parenting are predicted to be poor at regulating emotions which leads to less positive emotions, higher negative emotions, and behavioral problems [21]. However, another study conducted in Pakistan stated that authoritarian parenting is not significantly correlated with emotion regulation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in the ERICA have been largely unexplored, although Bunford and colleagues (2014) report a trend that girls may score higher than boys on the Self-Awareness subscale (although see Bunford, Evans, & Wymbs, 2015). Across a range of child and adolescent samples, the ERICA has been shown to demonstrate reasonable internal consistency (α's range from .81 to .75), construct validity, and test-retest reliability (Bunford et al, 2014;Herzog, Hill-Chapman, Hardy, Wrighten, & El-Khabbaz, 2015;MacDermott et al, 2010;Smith et al, 2016). Specifically in regards to emotion regulation strategies, the ERICA shows moderate positive correlations with self-reported cognitive reappraisal and small to moderate negative correlations with self-reported emotional suppression (Hughes, Gullone, & Watson, 2011).…”
Section: Measuring Self-reported Emotion Regulation In Adolescentsmentioning
confidence: 99%